2022
DOI: 10.3390/biology11010120
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter Defibrillator Multisensor Monitoring during Home Confinement Caused by the COVID-19 Pandemic

Abstract: Aims: The utilization of remote monitoring platforms was recommended amidst the COVID-19 pandemic. The HeartLogic index combines multiple implantable cardioverter defibrillator (ICD) sensors and has proved to be a predictor of impending heart failure (HF) decompensation. We examined how multiple ICD sensors behave in the periods of anticipated restrictions pertaining to physical activity. Methods: The HeartLogic feature was active in 349 ICD and cardiac resynchronization therapy ICD patients at 20 Italian cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…This is substantiated by the current low false negative event rate (0.17 per patient year) which is congruent with the previously reported false negative rate of 0.03 per patient year by Calò et al (10). The high negative predictive value and low false negative event rate make the HeartLogic TM algorithm very practical for clinical implementation, especially during the COVID-19 pandemic (21,22). In patients who are not in alert status, the outpatient visits may be converted to digital consults and/or lowered in frequency which is less burdensome for patients while they can rely on the fact that they are continuously monitored.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is substantiated by the current low false negative event rate (0.17 per patient year) which is congruent with the previously reported false negative rate of 0.03 per patient year by Calò et al (10). The high negative predictive value and low false negative event rate make the HeartLogic TM algorithm very practical for clinical implementation, especially during the COVID-19 pandemic (21,22). In patients who are not in alert status, the outpatient visits may be converted to digital consults and/or lowered in frequency which is less burdensome for patients while they can rely on the fact that they are continuously monitored.…”
Section: Discussionsupporting
confidence: 89%
“…True positive alerts [42 days ] lasted longer than false positive alerts [28 days (IQR 21-44)], p = 0.02. The maximal HeartLogic TM index was higher in true positive alerts [26][27][28][29][30][31][32][33][34]] compared to false positive alerts [19][20][21][22][23][24]], p < 0.01. Patients with higher HeartLogic TM indexes required more intense treatment (index height in outpatient setting 25 , day clinic treatment 28 and hospitalized patients 45 , respectively), p < 0.01.…”
mentioning
confidence: 99%
“…Ziacchi and colleagues reported a higher rate of alerts, suggesting the worsening of heart failure incidence. The weekly rate of alerts was significantly higher during the lockdown (1.56 alerts/week/100 pts) and after the lockdown (1.37 alerts/week/100 pts) compared to the pre-lockdown period (0.91 alerts/week/100 pts) [25]. In contrast, we found that in-office follow-up visits significantly decreased during the pandemic due to the enactment of the lockdown (p = 0.0077).…”
Section: Discussionmentioning
confidence: 82%
“…One study used self-reported step-count data from each subject's own, non-standardized smart device-based accelerometer [36]. Four Italian studies (individual sample sizes of 24, 180, 184, and 349 subjects) examining pandemic ICD accelerometry data observed reduced activity levels independent of pre-pandemic activity [56][57][58][59]. Our implantable cardiac device patients demonstrated more sedentary time as a result of the pandemic, mirroring the Italian experience, though they were subject to less strict lockdown mandates in the United States.…”
Section: Discussionmentioning
confidence: 99%